2003
DOI: 10.1007/s00442-003-1182-y
|View full text |Cite
|
Sign up to set email alerts
|

Does tree diversity increase wood production in pine forests?

Abstract: Recent experimental advances on the positive effect of species richness on ecosystem productivity highlight the need to explore this relationship in communities other than grasslands and using non-synthetic experiments. We investigated whether wood production in forests dominated by Aleppo pine (Pinus halepensis) and Pyrenean Scots pine (Pinus sylvestris) differed between monospecific and mixed forests (2-5 species) using the Ecological and Forest Inventory of Catalonia (IEFC) database which contains biotic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
5
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(87 citation statements)
references
References 26 publications
5
75
5
2
Order By: Relevance
“…Of studies that have been done, most find a positive relationship between diversity and function (Vilà et al 2007, Lei et al 2009, Paquette and Messier 2011, but see Vilà et al 2003), although few extend this relationship explicitly to services (e.g., Schwenk et al 2012, Gamfeldt et al 2013. Among studies that explicitly address C stocks, or storage, there is disagreement as to the nature of the correlation between C and forest biodiversity, with studies reaching different conclusions with respect to both the direction and magnitude of the relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Of studies that have been done, most find a positive relationship between diversity and function (Vilà et al 2007, Lei et al 2009, Paquette and Messier 2011, but see Vilà et al 2003), although few extend this relationship explicitly to services (e.g., Schwenk et al 2012, Gamfeldt et al 2013. Among studies that explicitly address C stocks, or storage, there is disagreement as to the nature of the correlation between C and forest biodiversity, with studies reaching different conclusions with respect to both the direction and magnitude of the relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies (Vilà et al, 2007) found that the dominant tree species is an important determinant for wood production in Spain. There are several factors that influence the relationships between species diversity and aboveground biomass productivity, such as environment (Hooper et al, 2005;Vilà et al, 2005;Ma et al, 2010;Paquette & Messier, 2011), spatial scale (Chase & Leibold, 2002), plant density (He et al, 2005;Potter & Woodall, 2014), successional status (Caspersen & Pacala, 2001;Vilà et al, 2003), site productivity (Paquette & Messier, 2011;Potter & Woodall, 2014), soil fertility (Rodríguez-Loinaz et al, 2008;Thoms et al, 2010), evolutionary history and latitude , and seed dispersal limitation .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Vennetier et al (2008) proved that P. halepensis was well adapted to the studied climatic zones and the obtained signif icant differences were supporting studies carried out in Tunisia (Khouja et al, 2000), Algeria (Harfouche et al, 2003;Bentouati and Bariteau, 2005) and Morocco (Belghazi et al 2000). Finally, the complexity of climatic influences on pine tree density resides in the structural and spatial distribution of pine trees (Vilà et al, 2003;Condés and Sterba 2008). It would be necessary to perform a general study on climate change and its impacts on natural forests in order to develop and apply silvicultural management tools adapted to the new scenarios and problems (Sabate et al, 2002), focusing on new objectives in sustainable forest management.…”
Section: Discussionmentioning
confidence: 99%